Am I cubic?

Algebra Level 4

We have a polynomial f ( x ) f(x) which satisfies the following conditions:

f ( 1 ) = 4 , f ( 2 ) = 3 , f ( 3 ) = 4 , f ( 4 ) = 7 f(1)=4~,~f(2)=3~,~f(3)=4~,~f(4)=7

Can f ( x ) f(x) be a cubic polynomial?

Note: This problem is original and is inspired by a facebook post .

Yes What? No It can and can't be simultaneously unless I give a proof. It's Schrodinger's f ( x ) f(x) . :P BATMAN! The answer is always batman! Can't say because given info isn't enough.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

5 solutions

Prasun Biswas
Jan 19, 2015

Let us assume that the given polynomial f ( x ) f(x) is cubic. Then, we can construct a difference table for f ( x ) f(x) using the given function values. The k th k^{\textrm{th}} difference column will be constant. The table comes out as follows:

n f ( n ) D 1 ( n ) D 2 ( n ) D 3 ( n ) 1 4 1 2 0 2 3 1 2 0 3 4 3 0 4 7 0 \begin{array} {c c c c c c c} n & f(n) & D_1(n) & D_2(n) & D_3(n)\\ 1 & 4 & -1 & 2 & 0\\ 2 & 3 & 1 & 2 & 0\\ 3 & 4 & 3 & & 0\\4 & 7 & & & 0\end{array}

We see that the elements of the column D 3 ( n ) D_3(n) are all 0 0 and we know that the k th k^{\textrm{th}} difference for the assumed cubic polynomial will be 3 ! 3! times the leading coefficient, i.e., coefficient of x 3 x^3 in the polynomial. But the k th k^{\textrm{th}} difference is 0 0 that we found out earlier.

Thus, the polynomial, if assumed cubic comes out as the form:

f ( x ) = 0 x 3 + a x 2 + b x + c f(x)=0\cdot x^3 + ax^2 + bx +c

Since coefficient of x 3 x^3 is 0 0 , the polynomial f ( x ) f(x) can never be cubic.

Hence, the answer is No.

Tijmen Veltman
Jan 26, 2015

Let g ( x ) = ( x 2 ) 2 + 3 f ( x ) g(x)=(x-2)^2+3-f(x) . If f f is a polynomial, then so is g g ; furthermore, g ( x ) = 0 g(x)=0 for x = 1 , 2 , 3 , 4 x=1,2,3,4 . A cubic polynomial (with non-zero leading coefficient) can't have four distinct roots; therefore g g is of degree 4 \geq 4 and hence so is f f . The answer, therefore is no \boxed{\text{no}} (although batman is close to the truth as well).

Chew-Seong Cheong
Jan 25, 2015

Assuming that f ( x ) f(x) is a cubic polynomial, we can write in matrix form:

X A = B [ 1 3 1 2 1 1 1 0 2 3 2 2 2 1 2 0 3 3 3 2 3 1 3 0 4 3 4 2 4 1 4 0 ] [ a 3 a 2 a 1 a 0 ] = [ 4 3 4 7 ] XA=B\quad \Rightarrow \begin{bmatrix} 1^3 & 1^2 & 1^1 & 1^0 \\ 2^3 & 2^2 & 2^1 & 2^0 \\ 3^3 & 3^2 & 3^1 & 3^0 \\ 4^3 & 4^2 & 4^1 & 4^0 \end{bmatrix} \begin{bmatrix} a_3 \\ a_2 \\ a_1 \\ a_0 \end{bmatrix} = \begin{bmatrix} 4 \\ 3 \\ 4 \\ 7 \end{bmatrix}

We can find A A as follows:

A = X 1 B = [ 1 6 1 2 1 2 1 6 3 2 4 7 2 1 13 3 21 2 7 11 6 4 6 4 1 ] [ 4 3 4 7 ] = [ 0 1 4 7 ] A = X^{-1}B = \begin{bmatrix} -\frac{1}{6} & \frac {1}{2} &-\frac {1}{2} & \frac {1}{6} \\ \frac {3}{2} & -4 & \frac {7}{2} &-1 \\ -\frac {13}{3} & \frac {21}{2} & -7 & \frac{11}{6} \\ 4 & -6 & 4 & -1 \end{bmatrix} \begin{bmatrix} 4 \\ 3 \\ 4 \\ 7 \end{bmatrix} = \begin{bmatrix} 0 \\ 1 \\ -4 \\ 7 \end{bmatrix}

It is shown that: f ( x ) = x 2 4 x + 7 f(x) = x^2-4x+7 showing that: N o \boxed{No} , it is not a cubic polynomial.

Lu Chee Ket
Jan 28, 2015

1 1 1 4

1 2 4 3

1 3 9 4

1 4 16 7

Since this 4 x 4 determinant is zero

1 1 1 1

1 2 4 8

1 3 9 27

1 4 16 64

and this 4 x 4 determinant is non zero of 12

f(x) = 7 - 4 x + x^2 + 0 x^3

Two points for a straight line, three points for a parabola and four points for a cubic curve and etc on a plane, where d = 0 tells that they cannot form a cubic curve but one among the four points is redundant or stays on parabola formed by 3 of them.

Hence, the answer is No.

Eilon Lavi
Jan 24, 2015

This is pretty cumbersome for this question, since we're given nice values, but it's a good general solution:

Lemma: There is at most one polynomial with degree n \le n that contains any n + 1 n+1 specific points

Suppose p ( x ) p(x) and q ( x ) q(x) have degree n \le n and contain ( x 1 , y 1 ) . . . ( x n + 1 , y n + 1 ) (x_1,y_1)...(x_{n+1},y_{n+1})

Then let r ( x ) = p ( x ) q ( x ) r(x)=p(x)-q(x) .

r ( x ) r(x) has degree n \le n and at least n + 1 n+1 zeros at x 1 , . . . , x n + 1 x_1,...,x_{n+1} . Thus r ( x ) = 0 r(x)=0 by the factor theorem. \square

You might recognize this polynomial as f ( x ) = ( x 2 ) 2 + 3 f(x) = (x-2)^2 +3 but again a systematic method:

We can brainlessly write

f ( x ) = 4 ( x 2 ) ( x 3 ) ( x 4 ) ( 1 2 ) ( 1 3 ) ( 1 4 ) + 3 ( x 1 ) ( x 3 ) ( x 4 ) ( 2 1 ) ( 2 3 ) ( 2 4 ) + 4 ( x 1 ) ( x 2 ) ( x 4 ) ( 3 1 ) ( 3 2 ) ( 3 4 ) + 7 ( x 1 ) ( x 2 ) ( x 3 ) ( 4 1 ) ( 4 2 ) ( 4 3 ) f(x)= 4 \dfrac{(x-2)(x-3)(x-4)}{(1-2)(1-3)(1-4)} + 3 \dfrac{(x-1)(x-3)(x-4)}{(2-1)(2-3)(2-4)} \\ + 4 \dfrac{(x-1)(x-2)(x-4)}{(3-1)(3-2)(3-4)} + 7 \dfrac{(x-1)(x-2)(x-3)}{(4-1)(4-2)(4-3)}

We don't actually need to evaluate this; we just need to check the x 3 x^3 coefficient:

4 ( 1 2 ) ( 1 3 ) ( 1 4 ) + 3 ( 2 1 ) ( 2 3 ) ( 2 4 ) + 4 ( 3 1 ) ( 3 2 ) ( 3 4 ) + 7 ( 4 1 ) ( 4 2 ) ( 4 3 ) \dfrac{4}{(1-2)(1-3)(1-4)} + \dfrac{3}{(2-1)(2-3)(2-4)} \\+ \dfrac{4}{(3-1)(3-2)(3-4)} + \dfrac{7}{(4-1)(4-2)(4-3)}

= 4 6 + 3 2 4 2 + 7 6 = 0 =-\dfrac{4}{6}+\dfrac{3}{2}-\dfrac{4}{2}+\dfrac{7}{6}=0

So this is not a cubic.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...